Management of Intracranial Neoplasms in Neurofibromatosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Recommendations are proposed for the diagnosis and management of CNS neoplasms with NF-1 and NF-2 at the Department of Neurology, Section of Pediatric Neurology, Cleveland Clinic Foundation, Cleveland, Ohio; Phoenix Children's Hospital, Phoenix, AZ; and Children's National Medical Center, George Washington University, Washington, D.C.